Integrated Learning: An Effective Model for Food Division Learning in Polytechnic - I Made Darma Oka; Ida Ayu Elistyawati; I Ketut Suarta (Universitas Pendidikan Ganesha, 2022)
The integrated practical learning process has not been comprehensively implemented in the Tourism Department yet. Therefore, it is considered necessary to improve the learning method. The study aims to analyses the effectiveness of integrated learning in the Food Division learning. The learning method which will be implemented action class experiment approach in which four courses, namely Food Production Operation, Restaurant and Bar Operation, Cost Control and English for Food Division are synergized under the same topic. The type of the research is classroom action research with student center learning approach. This current study applied the action class experiment approach in which two groups of samples were differently treated. The t-test, was used to test whether the learning achievement. The result of the test analysis showed that the implementation of the integrated practical learning process significantly contributed to accelerate the achievement of the competency of the students of the food division. Therefore, the integrated learning process is a highly effective one to be implemented in the vocational institution. The result of the statistical test showed that the competence achieved by the students with the integrated practical learning process was significantly different from that achieved by the students with the partial practical learning process. Therefore, it’s suggested to the management of the Tourism Department to motivate and facilitate the teaching staff especially those teaching the core courses to implement the integrated practical learning model to accelerate the achievement of competence in the learning materials taught to the students.